Azul de metileno associado com ureia na inativação fotodinâmica de bactérias periodontopatógenas - Miranda, Bianca Aparecida Godoy (2020)
Periodontal disease is an inflammatory response to oral biofilm and conventional treatment consists of scaling and root planing. As an adjunct to this treatment, antimicrobial photodynamic therapy (aPDT) has been proposed, which consists of the use of photosensitizer (FS) and light source for the formation of reactive oxygen species (Eros). However, there are difficulties in performing aPDT clinically and it is believed that this is due to the dye dimerization. Some authors report that in a surfactant, methylene blue decreases the tendency of dimerization. In addition, other studies show that the association of urea with methylene blue can decrease this dimerization, which would increase the effectiveness of the therapy. Thus, the objective of the study was to investigate the role of methylene blue vehicles in the photodynamic inactivation of periodontopathogenic bacteria, in addition to investigating the role of urea in the inactivation of periodontopathogens and the association of urea and surfactant in the inactivation of periodontopathogens. For this, A. actinomycetemcomitans (ATCC 29523) and P. gingivalis (ATCC 33277) were grown in microaerophilia and anaerobiosis for 48 h, respectively. Then, the experiments were carried out in triplicate, with 6 groups: 1) Control, without intervention 2) Light, only irradiated 3) FS, only the dye 4) PDT1, performed aPDT with 1 min of irradiation 5) PDT3, aPDT with irradiation of 3 min and 6) PDT5, aPDT with irradiation of 5 min. Methylene blue (AM) was used as a dye in the conventional form and surfactant in the presence of SDS (sodium dodecyl sulfate), with a final concentration of 100 µM, in addition to urea (U) with a final concentration of 2 M, and irradiated with laser λ = 660nm (Photon Lase lll, DMC, São Carlos, Brazil) with power of 100mW and radiant exposure 215J / cm2. After microbial growth, colony-forming units were counted. Optical absorption spectroscopy, which is the uptake analysis, was also performed to assess the absorbance spectrum. As a result, we observed that the control, light and FS groups of A. actinomycetemcomitans showed 1x109 cfu / mL and a microbial reduction of 7 orders of magnitude was achieved after 5 min of irradiation. In the control, light and FS groups of P. gingivalis, no significant differences were observed in relation to microbial decrease, but in the groups in which aPDT was performed, there was a difference in the pattern of microbial death with 3 and 5 min of irradiation showing complete reduction in groups with AM and AM-U-SDS. When analyzing the degree of incorporation of the dye, it is observed that A. actinomycetemcomitans incorporated 20% more than P. gingivalis in the AM and U-AM solutions. Regarding absorbance, P. gingivalis showed slightly higher absorption, and between the different media the absorption spectrum was similar. In view of the information presented, it is concluded that the different methylene blue vehicles assist in the photodynamic inactivation of periodontopathogenic bacteria and increase the effectiveness of aPDT in the described patterns, and the association of urea with methylene blue increases microbial death.